Menulis sebagai alternatif penangangan stress pada remaja - Zulfa, Intan Nala (Maliki Interdisciplinary Journal, 2025)
In the phenomena around us, it is not uncommon to find teenagers who need clinical treatment for their psychology or even end their lives due to difficulty adapting to the phase of entering early adulthood. Therefore, therapy and treatment are needed to prevent these bad things from happening. One of the therapies used is expressive writing therapy. This therapy asks a person to write down emotional experiences without time limits and with guidance from a therapist or counselor. In its application, this type of therapy method only requires a few tools in the form of books, journals or blogs to express one's feelings. This therapy has been proven to be an easy and effective alternative to relieve stress in teenagers. There are several types of writing models in this therapy, including free writing, writing without language rules, and writing for yourself. The expressive writing therapy process is carried out in three sessions, namely the opening session, writing session and closing session. The results of a study show that expressive writing therapy can help victims of domestic violence to overcome the psychological and physical problems they are experiencing. From this research it can be concluded that expressive writing therapy can be an effective alternative for dealing with stress in teenagers and can be done easily. This therapy can help teenagers reduce the levels of depression, anxiety and stress they experience. Therefore, expressive writing therapy can be a good choice to help teenagers deal with the stress they experience.